Implementing the Biodesign Process for Medical Device Innovation in Head and Neck Surgery. (December 2020) - Dharmawan, Rena; Ho, Henry; Ng, Harry Ho Man; Iyer, Narayanan Gopalakrishna; Tan, Hiang Khoon; Tan, Ngian Chye
Introduction. The Stanford Biodesign process is a needs-driven approach to innovation which begins in the clinical setting and environment and is championed by practicing clinicians and surgeons. Here, our team applied the Stanford Biodesign process through clinical immersion to identify potential unmet clinical needs in the field of head and neck surgery, brainstormed and prototyped solutions to solve the top unmet need, and developed a commercialized medical device. Methods. The team underwent the 3 phases of the Biodesign process: identify, invent, and implement. The team underwent clinical immersion and followed head and neck surgeons from the Department of Head and Neck Surgery for a duration of 1 month. The needs identified were then filtered through a structured process using predefined filters, and a top need was chosen. After multiple rounds of brainstorming and prototyping, a final concept was developed. Results. The team collected 111 unmet needs and designed the in vivo surgical lighting concept that eventually led to the development of the KLARO™ in vivo surgical lighting device with a commercial partner. KLARO™ is a fully flexible 4.6-mm diameter light-emitting diode light strip that is freely bendable to be safely placed into deep cavities during open surgeries. Conclusion. The Biodesign process provides a standardized way to turn these needs into solution to advance the field of head and neck surgery and improve the outcome of patients.